Diversity assessment of Gloriosa superba accessions from Western Ghats of India based on morphological traits, ISSR markers and metabolite content - Mahajan, Yogesh A.; Shinde, Balkrishna A.; Mulani, Fayaj A.; Gade, Akshay B.; Kasodekar, Amol K.; Thulasiram, H. V.; Kadoo, Narendra Y.; Nikam, Tukaram D. (Journal of Applied Research on Medicinal and Aromatic Plants, 2022)
Gloriosa superba L. (glory lily) is a medicinally and horticulturally important plant used as a commercial source of the alkaloid colchicine. The Western Ghats in India is mostly unexplored for the morphological, genetic, and metabolite diversity of the species. In the current study, three methodologies were employed to assess the diversity among 50 established accessions of G. superba collected from several locations in the Western Ghats. The morphological analysis revealed that, among the studied traits, seed yield per vine and dry seed weight per 100 seeds for the established accessions were the most diverse traits. The former exhibited a significantly positive correlation with four vegetative and five yield traits. The first three principal components showed nine traits contributing to the variation. Intra-specific molecular variation based on inter simple sequence repeat markers distributed the accessions in three clusters with high polymorphism and low genetic diversity indices. Liquid chromatography high-resolution mass spectrometry analysis revealed significant variation among the screened accessions for colchicine content in tuber and seed tissue. Interestingly, an unexplored tissue, pod shell, was found to contain significantly high colchicine, which could be explored for commercial colchicine extraction. The morphogenetic and metabolite variation revealed by the study would be useful to develop elite varieties to expand the cultivation of glory lily across the country, fulfilling the increasing demand for colchicine and providing remunerative income to the farmers.
Keywords: Colchicine; Genetic diversity; Gloriosa superba; Metabolite diversity; Morphological diversity; Western Ghats